Use of morphine in critically Ill COVID-19 patients: An ethics reflection - Jyothi Mariam Idiculla; Jananee Muralidharan; Sunita Simon Kurpad (Wolters Kluwer Medknow Publications, 2024)
The use of Morphine in terminal COVID is different from that in palliative care due to variable nature of the pandemic. In developing countries, the limitations in resources that can arise during a COVID wave, necessitates the availability of national guidelines for terminal care.